PENGARUH LATIHAN TENDANGAN DOLLYO CHAGI TERHADAP HASIL SPEED KICK PADA ATLET TAEKWONDO DOJANG TICC DI KABUPATEN BEKASI - Lumiaji Wijaya Dirgantara; Sungkowo Sungkowo (Universitas Negeri Semarang, 2023)
The purpose of this study was to determine the effect of dollyo chagi kick training on the results of speed kick dojang TICC in Bekasi Regency. This research is quantitative research with experimental research methods. The research design used is Pre-Experimental Design with a One-Group Pretest-Posttest Design model. The results of this study indicate a sig value (2 tailed) of 0.012 <0.05, so Ho is rejected and H1 is accepted. conclusions as follows: (1) There is a difference in the effect of pretest and posttest dollyo chagi kick training on speed kick results in taekwondo athletes Dojang TICC in Bekasi Regency. (2) The results show that the effect of dollyo chagi kicks on speed kick results is significant in Dojang TICC taekwondo athletes in Bekasi Regency.